Food preservation by cold plasma from dielectric barrier discharges in agri-food industries - Jiang, Hao; Lin, Qian; Shi, Wenqing; Yu, Xiuzhu; Wang, Shaojin (Frontiers in Nutrition, 2022)
Background Cold plasma (CP) can be defined as partially or wholly ionized gas carrying myriads of highly reactive products, such as electrons, negative ions, positive ions, free radicals, excited or non-excited atoms, and photons at ambient temperature. It is generated at 30–60°C under atmospheric or reduced pressure (vacuum). In contrast to thermal plasma, it requires less power, exhibits electron temperatures much higher than the corresponding gas (macroscopic temperature), and does not present a local thermodynamic equilibrium. Dielectric barrier discharges (DBD) are one of the most convenient and efficient methods to produce CP. Scope and approach Cold plasma technology has the potential to replace traditional agri-food processing purification methods because of its low energy requirements and flexible system design. CP technology works by reducing bacteria levels and removing pests and mycotoxins from your produce at harvest. It can also catalyze physiological and biochemical reactions and modify materials. It can meet microbial food safety standards, improve the physical, nutritional, and sensory characteristics of the products, preserve unstable bioactive compounds, and modulate enzyme activities. This manuscript also discusses the quality characteristics of food components before/after CP treatment. Key findings and conclusion In the past decade, CP treatments of food products have experienced increased popularity due to their potential contributions to non-thermal food processing. There is no doubt that CP treatment is a flexible approach with demonstrated efficacy for controlling many risks across food and agricultural sustainability sectors. In addition, CP technologies also can be applied in food-related areas, including modification of chemical structures and desensitization treatments. There is a need to fully assess the benefits and risks of stand-alone CP unit processes or their integration as a processing chain as soon as the economic, ecological, and consumer benefits and acceptability are considered.